The Origin of Capitalism - Wood, Ellen (Tantor Media, Inc., 2021)
How did the dynamic economic system we know as capitalism develop among the peasants and lords of feudal Europe? In The Origin of Capitalism, a now-classic work of history, Ellen Meiksins Wood offers a clear and accessible introduction to the theories and debates concerning the birth of capitalism, imperialism, and the modern nation state. Capitalism is not a natural and inevitable consequence of human nature, nor simply an extension of age-old practices of trade and commerce. Rather, it is a late and localized product of very specific historical conditions, which required great transformations in social relations and in the relationship between humans and nature.